Revisiting anti-tuberculosis therapeutic strategies that target the peptidoglycan structure and synthesis - Catalão, Maria João (2019)
This work was funded by a Research Grant 2018 of the European Society of Clinical Microbiology and Infectious Diseases (ESCMID) and Fundacao para a Ciencia e Tecnologia (FCT), Lisbon, Portugal, through research grant PTDC/BIA-MIC/31233/2017 awarded to MC.